Portal hypertension in acute liver failure. Issue 7 (July 1992) - Navasa, M; Garcia-Pagán, J C; Bosch, J; Riera, J R; Bañares, R; Mas, A; Bruguera, M; Rodés, J
Abstract : Twenty five patients with acute liver failure were measured for hepatic venous pressure gradient as an index of portal pressure during the course of a transjugular liver biopsy. Hepatic venous pressure gradient ranged from 4 to 24.5 mm Hg with a mean of 12.8 (5.3) mm Hg (normal values less than 5 mm Hg). All patients but one had increased portal pressure gradient. Portal hypertension correlated with the degree of architectural distortion of the liver, as suggested by a direct correlation between hepatic venous pressure gradient and the area of reticulin collapse, evaluated by means of a morphometric analysis on Sirius red stained liver slides (r = 0.43, p less than 0.05). Hepatic venous pressure gradient was significantly higher in patients with ascites (15.1 (5) mm Hg, n = 15) or renal failure (14.4 (5.3) mm Hg, n = 16) than in those without (9.3 (3.4) mm Hg and 10.1 (4) mm Hg, respectively; p less than 0.05). Portal hypertension was associated with systemic vasodilation and a hyperkinetic circulatory state, with decreased arterial pressure, and peripheral resistance and increased cardiac output.